Pulicaria vulgaris Gaertn. (Asteraceae) - A new species record for Bangladesh (Bangladesh Journal of Plant Taxonomy, 2011)
Not available.Keywords: Pulicaria vulgaris; New record; Bangladesh; Asteraceae.DOI: http://dx.doi.org/10.3329/bjpt.v18i2.9308Bangladesh J. Plant Taxon. 18(2): 205-208, 2011 (December)